1985
DOI: 10.1111/j.1365-2265.1985.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Changes of Serum Thyroglobulin and TSH in Residents of a Moderate Endemic Goitre Area

Abstract: Subjects living in iodine deficient areas were reported to have elevated serum thyroglobulin (Tg) concentrations. This finding was interpreted as related to thyroid stimulation. Discrepant results, however, were found when serum Tg concentrations were correlated either with serum TSH or with goitre size. In this study we investigated the relationships between goitre size, serum Tg and serum TSH in 488 unselected adult subjects living in an endemic area of North-Western Tuscany (Garfagnana district). The contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
5

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 23 publications
4
22
1
5
Order By: Relevance
“…This finding has already been observed in iodine deficient areas, such as those the majority of our patients came from, where longstanding iodine deficiency causes higher frequency of thyroid nodularity and autonomy in older people (Fenzi et al 1985, Vitti et al 1990, Aghini-Lombardi et al 1999. When patients were classified as affected by benign thyroid disease or PTC according to the results of cytology, the age-dependent reduction of TSH levels was highly significant in the first group, while in patients with PTC this phenomenon was much less evident.…”
Section: E Fiore Et Al: Tsh and Risk Of Ptcsupporting
confidence: 84%
“…This finding has already been observed in iodine deficient areas, such as those the majority of our patients came from, where longstanding iodine deficiency causes higher frequency of thyroid nodularity and autonomy in older people (Fenzi et al 1985, Vitti et al 1990, Aghini-Lombardi et al 1999. When patients were classified as affected by benign thyroid disease or PTC according to the results of cytology, the age-dependent reduction of TSH levels was highly significant in the first group, while in patients with PTC this phenomenon was much less evident.…”
Section: E Fiore Et Al: Tsh and Risk Of Ptcsupporting
confidence: 84%
“…Previous studies have reported elevated serum Tg in females (Cahoon et al, 2013;Fenzi et al, 1985;Giovanella et al, 2011;Knudsen et al, 2001;Thomson et al, 2001;Vejbjerg et al, 2009) and with attained age (Cahoon et al, 2013;Knudsen et al, 2001;Vejbjerg et al, 2009), while Giovanelli et al (2011 reported no difference in serum Tg by age in healthy individuals-suggesting that differences in serum Tg by age are due to thyroid dysfunction. We found higher serum Tg levels in females than males, and among older individuals in this study, which may be attributed to higher prevalence of thyroid diseases in these groups (despite adjusting for known thyroid abnormalities and dysfunction).…”
Section: Demographic Factors Thyroid Function and 131 I Thyroid Dosementioning
confidence: 88%
“…Of these, nine were randomized controlled trials, two were nonrandomized controlled trials, three were cohort observational studies, 23 were cross-sectional studies (10 multicenter), and one was a monitoring report of iodization programs that included a measurement before the introduction of iodized salt to a measurement after the introduction of iodized salt. In order to investigate the consistency of the relationship between iodine status as determined by UIC and Tg more clearly, for those studies that reported this information for more than one group, we considered each of these groups separately (i.e., one study of pregnant women and their newborns (37); one study of pregnant women and adults (38); one study of children and adults (30); three studies of children living in different regions (39) or countries (40,41); and seven studies of adults living in different regions (21,25,(42)(43)(44) or countries (45,46)). …”
Section: Search Strategymentioning
confidence: 99%
“…Seven studies (21,25,30,38,43,45,46) showed that iodine deficient adults had a median Tg ‡13 lg/L (range 16-69 lg/L), while only one study (45) reported that iodine-sufficient adults had a median Tg ‡ 13 lg/L. However, 8 of 12 studies (21,25,(42)(43)(44)72,90,91) reported that adults who were categorized as iodine deficient had a median Tg <13 lg/L. One of these studies (42) included adults with iodine excess (i.e., median UIC ‡300 lg/L) who, in contrast to the findings of Zimmermann et al (41) in schoolchildren, had a median Tg <13 lg/L.…”
Section: Adultsmentioning
confidence: 99%
See 1 more Smart Citation